Improving land readjustment practice. Application of management models to Portugal. Issue 7 (3rd July 2018) - Almeida, Joana; Ferreira, José Antunes; Condessa, Beatriz; Tomé, Ricardo
ABSTRACT: Whilst the advantages of the application of Land Readjustment (LR) are well known, there are nevertheless numerous countries in which application of LR is difficult or has not been successful. In its analysis of land readjustment constraints, conditions and the international practice, this paper contributes to improving the implementation of an LR system, particularly with respect to the management process. At the international level, management models in seven countries were studied: Australia, France, Germany, Japan, South Korea, Spain and Sweden. In Portugal, three case studies in the municipalities of Almada, Coimbra and Lisbon were selected, with semi-structured interviews being conducted with the respective managing entities. The management models are distinguished by the type of initiative and leadership processes, relations among stakeholders, managing entities and operating rules. It can be concluded that the role of the public authority as the process facilitator from the very initial stages, the existence of a managing entity and a board of specialists, and the legal conditions governing expropriation are key factors for the improvement of land readjustment management.